Analisis Hubungan Kausalitas Antara Pengangguran, UMK Dan Inflasi Di Kota Semarang Tahun 1993-2023 - Aura Febiliani Putri; Nenik Woyanti (FEB Universitas Sultan Ageng Tirtayasa, 2025)
The city of Semarang faces significant challenges, with the open unemployment rate reaching 5.99 percent in 2023. This situation arises from an imbalance between the available workforce and job opportunities, disparities between the minimum wage and the living wage, and inflation dynamics that impact the public's purchasing power. This study aims to empirically examine the causal relationship between the open unemployment rate (OUR), the city’s minimum wage (MW), and inflation (measured through the general consumer price index, or CPI) in Semarang. The study utilizes annual time series data on OUR, MW, and inflation spanning from 1993 to 2023, sourced from the BPS Statistics Indonesia. The analysis employed the Granger causality test and the Vector Error Correction Model (VECM) to assess the long-term relationships among the variables. Additionally, the Impulse Response Function (IRF) and Variance Decomposition (VD) were used to evaluate the impact of shocks throughout the analysis period. The findings reveal: 1) a unidirectional causal relationship from unemployment to inflation; 2) a unidirectional causal relationship from UMK to inflation; and 3) a bidirectional causal relationship between UMK and unemployment.